1984
DOI: 10.1111/j.1751-1097.1984.tb03426.x
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Action of Ultraviolet and Visible (Blue‐violet) Radiations at Defined Wavelengths on Human Lymphoblastoid Cells: Action Spectra and Interaction Sites

Abstract: The repair proficient human lymphoblastoid line (TK6) has been employed to construcr an action spectrum for the lethal action of ultraviolet (UV) radiation in the range 254-434 nm and to examine possible interactions between longer (334, 365 and 405 nm) and shorter wavelength (254 and 313 nm) radiations. The action spectrum follows a DNA absorption spectrum fairly closely out to 360 nm. As in previously determined lethal action spectra for procaryotic and eucaryotic cell populations. there is a broad shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…UVA radiation was provided by a broadspectrum (330-450 nm) Uvasun 3000 lamp (Mutzhas, F.R.G.) and dose rates were monitored as described (12). Irradiation times were <15 min and control dishes were sham-irradiated.…”
Section: Methodsmentioning
confidence: 99%
“…UVA radiation was provided by a broadspectrum (330-450 nm) Uvasun 3000 lamp (Mutzhas, F.R.G.) and dose rates were monitored as described (12). Irradiation times were <15 min and control dishes were sham-irradiated.…”
Section: Methodsmentioning
confidence: 99%
“…Vector DNA at a concentration of 1 p.g/ml in Tris-buffered saline (pH 7.5) was irradiated at room temperature with either germicidal UVC (254-nm) radiation or monochromnatic UVB (313-nm) radiation. Details of light sources, filtration, and dosimetry have been described previously (25). CV-1 cells at about 50% confluence were transfected with pZ189 DNA (50 ng per 9-cm petri dish) by using the DEAE-dextran method (15).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that irradiation of mammalian cells with violet or blue light induced H 2 O 2 production and DNA damage (1)(2)(3)(4)(5)(6)(7)(8)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Catalase and other antioxidants prevented this damage, indicating that H 2 O 2 production was a critical, early step in the process.…”
mentioning
confidence: 98%
“…Less recognized or understood is that toxicity can be induced by visible light. Specifically, violet (400-450 nm) and blue (450-490 nm) light are known to cause mutations and even death of cultured mammalian cells at irradiation doses of 2-6 J/cm 2 (1)(2)(3)(4)(5)(6)(7)(8), which is equivalent to 5-10 min of direct sunlight (9). Although most human cells are protected from sunlight by physical barriers (skin, hair, clothing), clinical pathologies resulting from intense sources of violet-blue light have been reported, e.g., solar retinopathy (10,11) and erythropoietic protoporphyria (12,13).…”
mentioning
confidence: 99%